Legal Standing on Health Workers in the Field of Emergencies and Disasters - Ginanjar, Anggi; Suryana, Ucup; Anggraeni, Happy Yulia (Research Horizon, 2025)
Health workers play a critical role in responding to medical emergencies and disasters. The legal responsibilities and obligations of health workers in these situations are often highlighted, both in terms of legal protection for health workers and their responsibility to save lives. This article will examine the legal standing of health workers in emergency and disaster scenarios. It will also examine the legal protection afforded to health workers in carrying out their duties, as well as the legal difficulties and issues they face in Indonesia. This research used normative legal research techniques and it used references from various national and international legal sources, as well as case studies, will be used for comparison. The legal standing of health workers in Indonesia, especially during emergencies and disasters, requires clearer and stricter rules to protect medical personnel on duty. Existing rules and regulations provide a legal framework, but in practice, health workers often face legal obstacles, especially in emergency situations and major disasters.